THE RELATIONSHIP BETWEEN PERSONAL HYGIENE AND SNACKING HABITS WITH THE INCIDENCE OF DIARRHEA IN CHILDREN - Nuraini Nuraini; Shinta Maharani; Latifah Latifah (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Diarrhea is a medical condition characterized by defecation more than 3 times a day, with liquid stools that may contain blood or body fluids, and vomiting. Diarrhea is influenced by various factors, such as personal hygiene (defecation habits, handwashing habits with soap, and hand and nail hygiene) and snacking habits. This study aims to analyze the relationship between personal hygiene and snacking habits with the incidence of diarrhea in children at SDN 114 Palembang. This study used a quantitative approach with a cross-sectional design. The population in this study amounted to 189 children, and 54 respondents were selected using a proportional random sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was carried out using univariate and bivariate tests with Fisher's Exact Test. The results showed that the majority of children with diarrhea (57.4%), poor snacking habits (72.2%), poor bowel habits (77.8%), poor handwashing habits with soap (64.8%), and poor hand and nail hygiene (74.1%). Bivariate analysis showed a significant association between snacking habits (p = 0.001), bowel habits (p = 0.018), and hand and nail hygiene (p = 0.008) and diarrhea. Meanwhile, there was no significant association between handwashing with soap and diarrhea (p = 0.774). The conclusion of this study is that snacking habits, bowel habits, and hand and nail hygiene are important factors that need to be considered to reduce the incidence of diarrhea in children.